Analisis dan Pengembangan Aplikasi Monitoring Proses Pengajuan Sertifikasi ISO Menggunakan Metode Scrum Berbasis Android - Sirojuddin Ahmad; Suryaningrat (shofanah Media Berkah, 2023)
Abstract− In the modern era, the use of information technology has become an essential component in almost all work activities. It not only serves as a tool but also plays a crucial role in enhancing productivity, creativity, and effectiveness. In the service industry, the utilization of information and communication technology is vital to ensure fast, effective, and efficient service delivery to customers. This study focuses on PT QAI Indonesia, a certification and training services company adhering to ISO standards. The company faces challenges with their manual certification registration process and the absence of a mobile-based certificate expiry reminder system. To address these issues, an information system was developed to streamline the registration process and enhance efficiency. The implementation of a mobile application allows clients to easily register and receive timely reminders for certification renewal. This case study demonstrates the effectiveness of using information technology to improve the certification process, leading to increased customer satisfaction and operational efficiency at PT QAI Indonesia. Keywords: ISO standards, certification process, information technology, efficiency, PT QAI Indonesia